2012
DOI: 10.1542/peds.2011-3114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acculturation and Distance From Cardiac Center on Congenital Heart Disease Mortality

Abstract: Further studies are needed to determine if these disparities in survival of infants with severe CHD are attributable to delays in referral to a cardiac center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 16 publications
5
57
1
Order By: Relevance
“…24,31,32,35 Children living 90-300 minutes from the cardiac centre were at significantly lower risk of unplanned readmission 29 compared with families living under 90 minutes away, but there was no association with mortality. 29,32 Family factors, including maternal education, marital status and country of birth, were not associated with adverse outcomes. 32 …”
Section: Individual and Family Factorsmentioning
confidence: 98%
See 4 more Smart Citations
“…24,31,32,35 Children living 90-300 minutes from the cardiac centre were at significantly lower risk of unplanned readmission 29 compared with families living under 90 minutes away, but there was no association with mortality. 29,32 Family factors, including maternal education, marital status and country of birth, were not associated with adverse outcomes. 32 …”
Section: Individual and Family Factorsmentioning
confidence: 98%
“…The review included eight retrospective reviews of surgical cases, [23][24][25][26][27][28][29][30] four retrospective cohort studies, [31][32][33][34] two case-control studies 35,36 and one randomised controlled trial that was reported in two papers. 26,37 Only three studies 29,36,37 included a prospective element.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations